2021
DOI: 10.1109/access.2021.3130889
|View full text |Cite
|
Sign up to set email alerts
|

Fault Identification of Photovoltaic Array Based on Machine Learning Classifiers

Abstract: Fault identification in Photovoltaic (PV) array is a contemporary research topic motivated by the higher penetration levels of PV systems in recent electrical grids. Therefore, this work aims to define an optimal Machine learning (ML) structure of automatic detection and diagnosis algorithm for common PV array faults, namely, permanent (Arc Fault, Line-to-Line, Maximum Power Point Tracking unit failure, and Open-Circuit faults), and temporary (Shading) under a wide range of climate datasets, fault impedances, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 53 publications
(124 reference statements)
0
8
0
2
Order By: Relevance
“…(3) Specificity TN TN FP (4) Based on the above metrics, we conduct G-mean and F1 as Eq. ( 5) and (6).…”
Section: Tp Tp Fpmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Specificity TN TN FP (4) Based on the above metrics, we conduct G-mean and F1 as Eq. ( 5) and (6).…”
Section: Tp Tp Fpmentioning
confidence: 99%
“…Abnormal events may thus frequently occur in IoT-based systems, such as low-voltage or voltage interruption events reducing sensor lifespan and performance [4]. In order to cope with this problem, some studies have suggested machine learning models and classification models to detect solar panel faults [5,6]. However, the amount of normal events is always very large, and abnormal events are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…Các phương pháp MLT áp dụng các mô hình trí tuệ nhân tạo hay máy học để huấn luyện và học nhận diện các đặc trưng của quá trình hoạt động của tấm pin xuyên suốt các tình trạng ổn định và sự cố. Các thông số được sử dụng để đưa vào các thuật toán máy học nhằm nhận diện sự cố có thể là các đặc tính I-V của hệ thống khi vận hành 14,15 hay sử dụng ảnh hồng ngoại kiểm tra tình trạng nhiệt của tấm pin quang điện 16 . Việc huấn luyện mô hình được thực hiện thông qua dữ liệu thu thập thực tế hay kết quả của các phép tính mô phỏng mô hình tấm pin quang điện.…”
Section: Phân Loại Sự Cố Mô-đun Quang đIện Dựa Trên đIểm Công Suất Cự...unclassified
“…15 sử dụng mô hình SVM với kernel GRB để đưa ra kết quả phân loại từ các thông số hoạt động của tấm pin gồm cường độ bức xạ, nhiệt độ, cường độ dòng điện và điện áp.Hình 9: Kết quả mô hình máy học dựa trên thuật toán k-means Hình 10: Kết quả mô hình máy học dựa trên thuật toán SVM Bảng 3:…”
unclassified
“…Most of the widely used identification methods for fault types are based on machine learning. Reference [1] identifies photovoltaic (PV) array faults based on machine learning structures which use three different classifier algorithms as comparisons. In [2], characteristic analysis algorithm is used and the association failure model is trained based on machine learning.…”
Section: Introductionmentioning
confidence: 99%